Contribution of Career Guidance, Internship Experience and Emotional Intelligence to the Work Readiness of Students at SMK N 1 SUTERA - Putra, Benny Adeka; Maksum, Hasan; Purwanto, Wawan; Waskito, Waskito (STKIP Singkawang, 2025)
This study aims to analyze the contribution of career guidance, industrial work experience (internship), and emotional intelligence to the work readiness of students at SMK N 1 Sutera. The background of this research is the high unemployment rate among vocational school graduates and the gap between their competencies and the needs of the industrial sector.Using a quantitative approach and survey method, the study involved 68 students who had participated in the internship program. Data were collected through questionnaires that had been tested for validity and reliability. The data were then analyzed using multiple linear regression.The results showed that career guidance significantly contributed to students’ work readiness with a correlation coefficient of r = 0.535 (R² = 28.6%, p = 0.000). This indicates that better career guidance helps improve students’ preparedness for the workforce. Internship experience also had a positive impact, with r = 0.351 (R² = 12.3%, p = 0.015), suggesting that hands-on industry experience increases students' readiness for real work environments. Emotional intelligence had the most dominant influence with r = 0.606 (R² = 36.8%, p = 0.000), showing that the ability to manage emotions and adapt socially plays a key role in preparing students for the workplace.Simultaneously, these three variables contributed 57.8% to students’ work readiness (R² = 0.578, F = 29.193, p = 0.000), meaning the research model is statistically significant. Therefore, schools and industries should enhance career guidance quality, improve the relevance of internship programs, and offer training to strengthen students' emotional intelligence, to better prepare them for the labor market and increase their competitiveness